JIGSAW METHOD IN ENGLISH TEACHING AND LEARNING - Dina Musriza; Elismawati Elismawati; Hidayat Al-Azmi (UIN Imam Bonjol Padang, 2021)
This paper describes the application of jigsaw method in English teaching and learning as a method that can enhance students interest in learning and enthuasism and become one of the effective and strategic method for teachers to apply in process of English teaching and learning. The methodology or approach used in this paper uses a library research., while the data collection is carried out by exploring and reviewing various journals, books, documents (printed and electronic) as well as other sources of data and information that related to the study. This paper analyzes several studies related to some topics of discussion. The findings in this study are jigsaw method has a good influence in increasing students interest in learning and improving students learning outcomes.